Permen Jeli dan Teh Celup: Produk Inovasi Daun Kelor sebagai Upaya Pemberdayaan Masyarakat di Kelurahan Klampok, Kecamatan Sananwetan Kota Blitar - Aji Putra, Chrystia; Christiano, Nicholas Raynato; Putra Parna, Dirgananda; Suryanita Pratiwi, Dewi (Journal of Applied Community Engagement, 2022)
Moringa (Moringa oleifera) is one of the plants that has nutritional content and many benefits, and its leaves can be used as innovative processed products. The purpose of this service activity is to increase the knowledge and skills of participants in processing Moringa leaves into jelly candy and tea bags. The method used in this service is by conducting surveys, product manufacturing practices, and providing material about products and their packaging through counseling. The results of this community service are members of PKK KWT Setia Abadi RT 03 RW 04 Klampok Village, Sananwetan District, Blitar City who look enthusiastic and have enthusiasm in receiving the material provided and are interested in practicing their own making innovations processed from Moringa leaves.